Abietane-Type Diterpenoids From Nepeta bracteata Benth. and Their Anti-Inflammatory Activity - Yang, Er-Lan; Hou, Yong; Ma, Guo-Xu; Zou, Lin-Jun; Xu, Xu-Dong; Wu, Hai-Feng; Yang, Jun-Shan; Wei, Hong-Wan; Fan, Cong-Zhao; Sun, Zhao-Cui; Shi, Lei-Ling (Frontiers in Chemistry, 2022)
Terpenes possess a wide range of structural features and pharmaceutical activities and are promising for drug candidates. With the aim to find bioactive terpene molecules, eight new compounds were isolated from the medicinal plant Nepeta bracteata Benth., including seven new abietane-type diterpenoids (1−7), along with a new ursane-type triterpenoid (8). The structures of compounds 1−8 were elucidated through the detailed spectroscopic analyses of their 1D and 2D NMR and MS data, and the absolute configurations of compounds 1-7 were determined by comparing their experimental and calculated ECD spectra. Compound 1 was a novel degraded carbon diterpene with the disappearing of methyl signal at C-19, while compound 7 possessed a new norabietane-type diterpenoid carbon skeleton with the presence of five-membered lactone arising from ring rearrangement. The anti-inflammatory of all obtained isolates were evaluated on lipopolysaccharide (LPS)-stimulated RAW 264.7 cells and the results of anti-inflammatory activity screening showed that compared with the LPS model group, all compounds were significantly down-regulation the TNF-α inflammatory factor at the specific concentration, except for compound 6.